Studying the technology stack and processes of software companies located in Iceland - Helgi Sævar Þorsteinsson 1997- (2020)
This paper describes the research results regarding the technology stack and software processes of Icelandic companies in 2020. The participants of the research are working professionals in the software industry in Iceland. The research was conducted in the fall of 2020. The number of software companies working in Iceland is growing every year. Today, more than 800 software companies are working in Iceland. The variety among IT companies is substantial, with different products targeting different markets being developed using large numbers of different software tools and programming languages, following different processes. For students and startups, this variety can be confusing since there is no clear direction for best using their resources to develop a professional portfolio or a product that best fits the market. For researchers, projects might not have the desired impact due to similar reasons. This paper describes the research results regarding the technology stack and software processes of Icelandic companies in 2020. The participants of the research are working professionals in the software industry in Iceland. The research was conducted in the fall of 2020. The purpose was to get a clear overview of what progress and technology tools software companies in Iceland use to create software. The results draw an overview of the most popular tech stack in Iceland and how the software companies develop software. This paper discusses how the survey came about, how it was conducted, and the main results. An online survey was sent out to carefully chosen professionals working in the software industry in Iceland. The respondents were asked to answer questions regarding what sector they were working in, what processes and tools they use to create software in their working environment. Furthermore, the study covered basic questions on how the company they work for operates. The survey was sent out to 100 companies. Out of them, we received 50 answers. This paper’s main findings are that there are many similarities ...